Severe Hematoma of Vulva after Vulvar Varicose Vein Surgery - Kokanalı, Kuntay; Kokanalı, Demet; Pabuçcu, Emre Göksan (Gynecology Obstetrics & Reproductive Medicine, 2014)
Vulvar hematomas, causing serious morbidity and rarely mortality, usually occur after delivery. Non obstetric ones are rare conditions which is often seen after blunt trauma of vulva. Management of vulvar hematoma include conservative and surgical approaches. Surgical methods are prefered for great, complicated, expanding ones especially. We present a severe vulvar hematoma happened after vulvar varicose vein surgery and discuss the conservative approach for this case.